Kualitas Napas Di Tengah Serbuk Kain: Korelasi Lama Paparan Debu Dan Fungsi Paru Pada Pekerja Konveksi - Rhandy Bane Umbu Dongu Deddi; Yuswanto Setyawan (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2025)
Breath Quality Amidst Fabric Dust: Correlation Between Dust Exposure Duration And Pulmonary Function Among Convection Workers Abstract                                                                                               Occupational exposure to dust in the garment industry has been associated with the risk of impaired pulmonary function among workers. This study aims to examine the correlation between the duration of dust exposure and lung function status among convection workers. A cross-sectional quantitative approach was used, involving 100 workers from garment industries in Sidoarjo. Subjects were selected using purposive sampling, considering inclusion criteria such as active employment status, no prior diagnosis of chronic lung disease, and minimum one year of working experience. Pulmonary function was measured using spirometry, classifying results into normal and obstructive impairment. The chi-square and Spearman correlation tests were applied to assess associations between variables. Findings showed that 72% of respondents were aged 30–50 years, 58% had worked for more than 5 years, and 65% were female. Among workers with less than 5 years of exposure, only 30% had obstructive pulmonary disorders. In contrast, 55% of those exposed for 5–10 years and 70% of those exposed for more than 10 years experienced impaired lung function. The chi-square test revealed a significant association between duration of exposure and pulmonary function (χ² = 11.11; p = 0.001), while the Spearman test confirmed a moderate positive correlation (r = 0.41; p < 0.01). These findings highlight the importance of occupational health surveillance and the implementation of adequate protective equipment in garment industries to minimize respiratory risks. Monitoring lung function regularly can assist in early detection and prevention of chronic pulmonary conditions among textile workers. Keywords: dust exposure; pulmonary function; convection worker; occupational health; chi-square test Abstrak Paparan debu dalam industri konveksi telah dikaitkan dengan peningkatan risiko gangguan fungsi paru pada pekerja. Penelitian ini bertujuan untuk menganalisis hubungan antara lama paparan debu dengan status fungsi paru pada pekerja konveksi. Pendekatan kuantitatif dengan desain potong lintang digunakan dalam penelitian ini yang melibatkan 100 pekerja konveksi di wilayah Sidoarjo. Subjek dipilih secara purposive dengan kriteria inklusi seperti status kerja aktif, tidak memiliki riwayat penyakit paru kronis, dan pengalaman kerja minimal satu tahun. Fungsi paru diukur menggunakan spirometri dan diklasifikasikan menjadi normal serta gangguan obstruktif. Analisis data dilakukan menggunakan uji chi-square dan korelasi Spearman. Hasil menunjukkan bahwa 72% responden berusia 30–50 tahun, 58% telah bekerja lebih dari 5 tahun, dan mayoritas berjenis kelamin perempuan (65%). Pada pekerja dengan paparan <5 tahun, hanya 30% yang mengalami gangguan paru. Sebaliknya, 55% dari kelompok paparan 5–10 tahun dan 70% dari kelompok >10 tahun mengalami gangguan fungsi paru. Uji chi-square menunjukkan adanya hubungan signifikan antara lama paparan dan fungsi paru (χ² = 11,11; p = 0,001), dan uji Spearman menunjukkan korelasi positif sedang (r = 0,41; p < 0,01). Temuan ini menekankan pentingnya pemantauan kesehatan kerja dan penggunaan alat pelindung diri yang memadai dalam industri konveksi untuk mengurangi risiko gangguan pernapasan. Pemeriksaan fungsi paru secara berkala diperlukan untuk deteksi dini dan pencegahan kondisi paru kronis pada pekerja tekstil. Kata Kunci: paparan debu; fungsi paru; pekerja konveksi; kesehatan kerja; uji chi-square